Karakterisrik Fisiko-Kimia dan Sensoris Sosis Ikan Gabus dengan Kombinasi Jamur Tiram (Pleorotus sp.) - Muhamad Iqbal; Agus Supriadi; Rodiana Nopianti (Jurnal FishtecH, 2015)
The purpose of this research was to know the characteristics physic, chemical, and sensory fish sausage of snakehead with a combination of oyster mushrooms. This research method using a Random Block Design (RBD). The parameters observed were gel strength and whiteness, water content, ash, fat, protein and crude fiber and sensory analysis include the quality hedonik and folding test. The results showed if the addition of oyster mushroom effect on gel strength and whiteness. For gel strength values from 143.33 to 475.43 gf, whiteness 54.52 to 70%. The best treatment quality fish sausage of snakehead with a combination of oyster mushrooms was the treatment with (95% snakehead and 5% oyster mushrooms). Besides the addition of oyster mushrooms on sausages provide fiber that useful for the body. The examination chemical testing addition of oyster mushrooms increase all observed from the water, ash, protein, fat and crude fiber.